Structure of Integrated Stability Monitoring in Open Pit Mining Using Digital Technologies - Rybin, V. V.; Konstantinov, K. N.; Nagovitsyn, O. V. (Journal of mining science, 2021)
The newly presented structure of integrated monitoring includes geological and geotechnical conditions of mineral mining, peculiarities of the production and infrastructure objects, as well as specifications and manuals of measurement tools. The monitoring-embraced hazardous objects are listed and grouped. Each group of the hazardous objects is described with the common features, properties, criteria and other characteristics meant for the monitoring supervision toward efficient and faultless operation. A prototype monitoring system for instability of mine objects is implemented using mining and geological information system MINEFRAME, and the data base on the objects of monitoring is composed.